Clasificación secuencial tecno-tipológica de las fíbulas de codo de la Península Ibérica. - Carrasco Rus, Javier; Esquivel Guerrero, José A.; Aranda, Gonzalo; Pachón Romero, Juan Antonio (Complutum, 1999)
Sin resumen